The staging of venture equity capital and venture capitalist bargaining power - G. Geoffrey Booth; Orkunt Dalgic; Allan Young (The Journal of Entrepreneurial Finance and Business Ventures, 2004)
In this paper we look at the effects of bargaining power on the types of entrepreneurial projects chosen by venture capitalists and show that a wealth-constrained venture capitalist prefers to provide equity financing to a two-stage rather than to a similar single-stage project. While the venture capitalist does not have bargaining power over the entrepreneur of a single-stage project and is thus unable to extract any surplus, the venture capitalist does have this advantage in a two-stage project and, provided the project is good, can demand a portion of the surplus as a pre-condition for providing follow-on capital. This suggests that venture capitalists should stage their capital investments in order to improve their bargaining power, allowing them to earn greater profits from successful entrepreneurial projects.
Keywords: 650